2020
DOI: 10.1111/ans.16470
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐guided foam sclerotherapy for primary small saphenous vein insufficiency

Abstract: This study shows that ultrasound‐guided foam sclerotherapy is a safe and effective method for symptomatic small saphenous vein insufficiency, with less adverse reactions and better effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…The majority of truncal vein treatments involve foam polidocanol with a concentration ranging from 1% to 3%. The hyperpigmentation rates reported by all RCTs and non‐RCTs during this analysis (liquid and foam) were 7%–45.8% for polidocanol 1%, 21–26 16%–17% for polidocanol 2% 27,28 and 7.4%–32.5% for polidocanol 3% 21,22,24,25,28–30 …”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…The majority of truncal vein treatments involve foam polidocanol with a concentration ranging from 1% to 3%. The hyperpigmentation rates reported by all RCTs and non‐RCTs during this analysis (liquid and foam) were 7%–45.8% for polidocanol 1%, 21–26 16%–17% for polidocanol 2% 27,28 and 7.4%–32.5% for polidocanol 3% 21,22,24,25,28–30 …”
Section: Resultsmentioning
confidence: 72%
“…The hyperpigmentation rates reported by all RCTs and non-RCTs during this analysis (liquid and foam) were 7%-45.8% for polidocanol 1%, [21][22][23][24][25][26] 16%-17% for polidocanol 2% 27,28 and 7.4%-32.5% for polidocanol 3%. 21,22,24,25,[28][29][30] One randomized study compared polidocanol 3% liquid and polidocanol 3% foam. The authors found slightly less hyperpigmentation in the foam group than in the liquid group (7.4% vs. 9.6%) with almost the same injected volumes (liquid or emulsified foam).…”
Section: Telangiectasia and Reticular Varicose Veinsmentioning
confidence: 99%
“…El 60.9% de los pacientes reportó uso adherente de elastocompresión, ligeramente más alto a lo encontrado en otros trabajos donde se mencionan adherencias alrededor del 40 al 50% 18,19 . Se considera importante este hallazgo en esta población, dado que este es un factor protector para la progresión de la enfermedad venosa, como bien ha sido mencionado en otros trabajos e, incluso, en las guías de manejo internacional recientes [1][2][3][4] .…”
Section: Discussionunclassified